Design, synthesis and SAR study of novel C2-pyrazolopyrimidine amides and amide isosteres as allosteric integrase inhibitors. Issue 21 (1st November 2020) - Patel, Manoj; Cianci, Christopher; Allard, Christopher W.; Parker, Dawn D.; Simmermacher, Jean; Jenkins, Susan; Mcauliffe, Brian; Minassian, Beatrice; Discotto, Linda; Krystal, Mark; Meanwell, Nicholas A.; Naidu, B. Narasimhulu
Graphical abstract: The design, synthesis and structure–activity relationships associated with a series of C2-substituted pyrazolopyrimidines as potent allosteric inhibitors of HIV-1 integrase (ALLINIs) are described. Structural modifications to these molecules were made in order to examine the effect on potency and, for select compounds, pharmacokinetic properties. We examined a variety of C2-substituted pyrazolopyrimidines and found that the C2-amide derivatives demonstrated the most potent antiviral activity of this class against HIV-1 infection in cell culture. Abstract: The design, synthesis and structure–activity relationships associated with a series of C2-substituted pyrazolopyrimidines as potent allosteric inhibitors of HIV-1 integrase (ALLINIs) are described. Structural modifications to these molecules were made in order to examine the effect on potency and, for select compounds, pharmacokinetic properties. We examined a variety of C2-substituted pyrazolopyrimidines and found that the C2-amide derivatives demonstrated the most potent antiviral activity of this class against HIV-1 infection in cell culture.